2022
DOI: 10.1021/acs.jmedchem.2c00704
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of BLU-945, a Reversible, Potent, and Wild-Type-Sparing Next-Generation EGFR Mutant Inhibitor for Treatment-Resistant Non-Small-Cell Lung Cancer

Abstract: While epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have changed the treatment landscape for EGFR mutant (L858R and ex19del)-driven non-small-cell lung cancer (NSCLC), most patients will eventually develop resistance to TKIs. In the case of first- and second-generation TKIs, up to 60% of patients will develop an EGFR T790M mutation, while third-generation irreversible TKIs, like osimertinib, lead to C797S as the primary on-target resistance mutation. The development of reversible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Currently, to combat mutations like C797S and T790M, fourth-generation EGFR-TKIs are being created. BLU-945 and OBXOZ-011 have shown good results against C797S and T790M mutants in preclinical studies (Eno et al, 2022). In addition, combination therapy can overcome resistance caused by C797S mutations.…”
Section: Target Drugs Clinically Used Drug Resistance Mechanismsmentioning
confidence: 99%
“…Currently, to combat mutations like C797S and T790M, fourth-generation EGFR-TKIs are being created. BLU-945 and OBXOZ-011 have shown good results against C797S and T790M mutants in preclinical studies (Eno et al, 2022). In addition, combination therapy can overcome resistance caused by C797S mutations.…”
Section: Target Drugs Clinically Used Drug Resistance Mechanismsmentioning
confidence: 99%
“…Additionally, the in vivo antitumor activity of BLU-701 (a fourth-generation EGFR-TKI) against the C797S resistance mutation has been demonstrated in a PC9 cell line-derived tumor xenograft model [124,125]. The phase I/II SYMPHONY clinical trial (NCT04862780) is evaluating the safety and anticancer activity of BLU-945 against the EGFR-sensitized mutation/T790M/C797S [126][127][128]. Recently, circulating tumor DNA (ctDNA) analysis revealed that BLU-945 achieved a median 48% reduction in EGFR resistance mutations (T790M and C797S), which represented emerging evidence of the efficacy of BLU-945 [129].…”
Section: Next-generation Egfr Allosteric Inhibitorsmentioning
confidence: 99%
“…Medicinal chemistry efforts have recently demonstrated that the detrimental effect of C797S mutation can be overcome. , Compounds able to occupy accessory pockets in the kinase active site of EGFR, forming an extensive network of polar interactions with the catalytic lysine of EGFR (Lys745) and neighboring residues, have been reported to display an exceptional affinity for EGFR C797S variants . Different compounds exploiting this approach have been described lately, including the clinical candidate BLU-945, reported to block EGFR L858R/T790M/C797S in animal models …”
Section: Introductionmentioning
confidence: 99%
“…12 Different compounds exploiting this approach have been described lately, 13 including the clinical candidate BLU-945, reported to block EGFR L858R/T790M/C797S in animal models. 14 An alternative strategy to target EGFR variants insensitive to osimertinib is represented by the development of covalent agents targeting a residue distinct from Cys797. 15 The catalytic lysine of EGFR has attracted growing attention in the discovery of next-generation TCIs in light of its unique chemical and biological properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation